2020
DOI: 10.1101/2020.10.12.20211706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of statistical methods used in the analysis of interrupted time series studies: a simulation study

Abstract: Interrupted time series (ITS) studies are frequently used to evaluate the effects of population level interventions or exposures. To our knowledge, no studies have compared the performance of different statistical methods for this design. We simulated data to compare the performance of a set of statistical methods under a range of scenarios which included different level and slope changes, varying lengths of series and magnitudes of autocorrelation. We also examined the performance of the Durbin-Watson (DW) te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…For longer series, as expected, the confidence intervals are narrow, with many excluding no and negative autocorrelation estimates. for autocorrelation (which OLS does not), and in a numerical simulation study investigating the performance of these methods, PW was shown to perform better than OLS for data series approximately longer than 24 points (12). The results in our empirical investigation therefore likely reflect the influence of shorter data series.…”
Section: Autocorrelation Coefficient Estimatesmentioning
confidence: 59%
See 4 more Smart Citations
“…For longer series, as expected, the confidence intervals are narrow, with many excluding no and negative autocorrelation estimates. for autocorrelation (which OLS does not), and in a numerical simulation study investigating the performance of these methods, PW was shown to perform better than OLS for data series approximately longer than 24 points (12). The results in our empirical investigation therefore likely reflect the influence of shorter data series.…”
Section: Autocorrelation Coefficient Estimatesmentioning
confidence: 59%
“…< 100 data points), with the ARIMA and OLS autocorrelation estimates being substantially smaller than REML. Given the true underlying autocorrelation would not be expected to vary by series length, the stability of the REML estimates over the different series lengths is suggestive of it being the preferable estimator, which has been shown in numerical simulation studies to be the case (12,26).…”
Section: Autocorrelation Coefficient Estimatesmentioning
confidence: 90%
See 3 more Smart Citations